2015
DOI: 10.1016/s2095-3119(14)60824-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gallic acid on porcine neutrophils phosphodiesterase 4, IL-6, TNF-α and rat arthritis model

Abstract: Our previous studies showed the anti-inflammatory effects of Paeonia lactiflora roots extract may be mediated, at least in part, through its gallic acid content, and this effect may be regulated in part by an inhibition on cAMP-phosphodiesterase (PDE). To explore the anti-inflammatory effect and mechanism, we further studied the influence of gallic acid on neutrophils PDE4 activity and expression, TNF-α and IL-6 content and rat arthritis model. PDE4 activity and gene express was calculated respectively by subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 20 publications
1
3
0
2
Order By: Relevance
“…The inflammatory response and oxidative stress exacerbate the deleterious effects of infections. Phenolic compounds have been reported to interact with the inflammatory response (Jiang et al, 2015). Several studies have revealed that phenolic compounds are capable of enhancing host immunity to prevent some infectious diseases.…”
Section: Plasma Metabolitesmentioning
confidence: 99%
“…The inflammatory response and oxidative stress exacerbate the deleterious effects of infections. Phenolic compounds have been reported to interact with the inflammatory response (Jiang et al, 2015). Several studies have revealed that phenolic compounds are capable of enhancing host immunity to prevent some infectious diseases.…”
Section: Plasma Metabolitesmentioning
confidence: 99%
“…Thus, gallic acid can modulate pro-inflammatory gene expression and cytokine production. The in vivo experiments showed that extracts containing gallic acid together with other polyphenols had a clear restrictive effect on local inflammation in the animal model ( p < 0.05) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a significant reduction of proinflammatory cytokines (TNF-α, IL-1β) in the joints of rats treated by LfAE at doses of 200 and 300 mg/kg. According to previous reports, gallic acid can suppress the release of TNF-α by neutrophis, which appear to be related to its inhibitory effect on cAMP-phosphodiesterase 4 activity [33]. Additionaly, Ahad et al [34] suggested that ellagic acid can suppress the synthesis of IL-1β and TNF-α by inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%